2021
DOI: 10.1108/jfra-05-2020-0143
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting and market value growth of quoted companies in Nigeria

Abstract: Purpose This study aims to examine the effect of sustainability reporting on market value growth (MVG) of quoted companies in Nigeria. The corporate reporting system has evolved, and this study examined how it influences the perception of investors. Design/methodology/approach This study adopted an ex post facto research design with 167 listed firms as the population. A total of 28 quoted firms were chosen with the use of purposive sampling. Data from 2009 to 2018 were obtained from secondary sources. Conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This contradicts the outcome by Lopez et al (2007), Financially material sustainability reporting who also use DSJI membership as a proxy of sustainability practice and find a negative relationship between sustainability reporting and financial performance. More recently, Taiwo et al (2021) study the impact of sustainability reporting on firm performance in Nigeria and document no significant relationship.…”
Section: Sustainability Reporting and Firm Performancementioning
confidence: 99%
“…This contradicts the outcome by Lopez et al (2007), Financially material sustainability reporting who also use DSJI membership as a proxy of sustainability practice and find a negative relationship between sustainability reporting and financial performance. More recently, Taiwo et al (2021) study the impact of sustainability reporting on firm performance in Nigeria and document no significant relationship.…”
Section: Sustainability Reporting and Firm Performancementioning
confidence: 99%
“…A few studies reported that the extent of sustainability and SDGs disclosure is gradually increasing in the region (Arthur et al, 2017; Bananuka, Tauringana, & Tumwebaze, 2022; Injeni et al, 2021; Kabir & Akinnusi, 2012; Soobaroyen et al, 2023; Stolowy & Paugam, 2018; Tumwebaze et al, 2022). The vast majority, however, denied this evidence and rather noted that the extent of reporting in the continent is very low and unsatisfactory (Ahmad & Gao, 2005; Akrout & Ben Othman, 2016; Alshbili et al, 2020; Amoako et al, 2017; Baba & Baba, 2021; Bhatia & Makkar, 2020; Bose & Khan, 2022; Crous et al, 2021; Erin & Bamigboye, 2022; Haladu & Bin‐Nashwan, 2022; Iredele, 2020; Lauesen, 2016; Marx & van Dyk, 2011; Mathuva & Kiweu, 2016; Taiwo et al, 2021; Tilt et al, 2021).…”
Section: Thematic Analysismentioning
confidence: 99%
“…Mathuva and Kiweu (2016) explained the negative association as a result of the altered regulatory environment or as a sign that businesses are shifting to financially (profit) focused goals. In comparison, the last group of studies has failed to support the association between the two factors (Asogwa et al, 2020; Moses et al, 2014; Taiwo et al, 2021). Furthermore, Mohamed Buallay et al (2021) reported that sustainability reporting negatively affects the operational performance and market performance of banks in Africa while positively associated with financial performance.…”
Section: Thematic Analysismentioning
confidence: 99%
“…In practice, sustianability report helps strengthen its reputation by building positive image in the eyes of the stakeholders (Misiuda and Lachmann, 2022). Here, the quality of sustainability reporting is very crucial (Taiwo et al, 2022), especially in communicating their performance and contribution to sustainable development that works as a positive signal to improve their reputation (Hahn and Kühnen, 2013).…”
Section: Bank's Reputation Mediating Effect Between Sustainability Re...mentioning
confidence: 99%